Midline extraperitoneal approach to retroperitoneal pathology ‐ broadening the horizons. Issue 11 (21st August 2022) - Kovacic, James; Hanna, Bishoy; McCombie, Steve; Vass, Justin; Ferguson, Richard; Winter, Matthew
Abstract : We present an explanation of approach to open midline extraperitoneal surgery for the management of retroperitoneal pathology. Included are diagrammatic and intra‐operative images to better explain the approach, as well as discussion regarding the technique.